PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA EMPRESA DE EMPACADO AL VACÍO DE LEGUMBRES, EN LA CIUDAD DE SARAGURO, PROVINCIA DE LOJA - Contento Japón, Delia Carmen (2016)
The research is intended to make a "PROJECT FEASIBILITY FOR THE IMPLEMENTATION OF A COMPANY OF VACUUM PACKED VEGETABLES IN THE CITY OF SARAGURO, Loja province, the purpose of this business idea is to offer consumers a pollution-free product that can be exploited at maximum freshness, without the presence of rootlets or bad condition of the goods. Whose main objective is to develop an investment project to determine the feasibility of vacuum packed and tender bean to market in the town of Saraguro beans. To achieve the objectives methods, deductive and inductive in order to analyze and synthesize information obtained from the different studies was used. The techniques of observation and survey, through instruments such as the observation guide and questionnaire allowed to obtain valid information for the study. The results can be established that the potential demand for the products is 2,535 families, the real demand is for 2,269 families who consume beans and broad beans, effective demand is 176,101 pounds, also established that there is a company dedicated to this activity therefore supply is zero. On the technical study determined that the installed capacity is 525,600 pounds per year, and capacity utilization is 125,280 pounds a year, also established that the project location is in the City of Saraguro streets, in Avda. March 10 and Queen Quito opposite the mall. 5 The financial study showed that the investment amounts to $ 23,269.39, which will be financed by the partners and 53.46% by the National Development Bank 46.54%. Financial indicators determined the profitability of the project as it is shown: the NPV of $ 38,089.23 the result is positive therefore is feasible investment and IRR of 71.85%, is higher than the rate of opportunity, the same which is 16%, so the project is feasible, the benefit is I consist of 0.25 cents which means for every dollar invested 0.25 cents receive, the investment is recovered in one year 4 months and 9 days and the sensitivity analysis with increased costs of 14.86% and 11.87% in the declining revenues, these values do not affect changes in project costs and revenues. The conclusions that have been reached are: the analysis of the market study was to identify the feasibility of the project, according to studies of supply, demand and marketing plan, this project gets a good return on all stages of their development, so that its execution is feasible. Recommendations: It is done a good advertising campaign, with the aim of making known the products, this study is likely to run, so it is recommended to implement the company.